Masyarakat Bakateu Hidup Dalam Keberagaman Tanpa Konflik Selama 45 Tahun - Marianus Teti (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2021)
This study aims to determine how the life of Catholic-Muslim harmony for 45 years in Bakateu. The research method used is qualitative research with a qualitative descriptive approach. The study was conducted for six months (January-June 2018). There are four things that have made the Bakateu community survive for 45 years and there have never been any conflicts between religious believers, namely the spirit of kinship, the spirit of friendship and service, the spirit of solidarity and the spirit of mutual cooperation. These four things happen because of the existence of a communication of the soul so that peace, harmony, mutual respect and respect for one another are maintained and maintained by the Bakateu community as a cultured and religious society. There is no conflict between religious believers due to the spirit of kinship, the spirit of friendship and service, the spirit of solidarity and the spirit of mutual cooperation which has been fostered since the beginning of diversity until now. I hope there are other researchers who can carry out further research or development research to see further about the other impacts of inter-religious relations in Bakateu and elsewhere.